Evaluation of cytotoxic T-cell activation, chemokine receptors, and adhesion molecules in blood and serum in patients with oral lichen planus - NAMDAR PEKİNER, FİLİZ MEDİHA; BORAHAN, MEHMET OĞUZ (WILEY, 2012)
J Oral Pathol Med (2012) 41: 484489 Background: Our purpose is to study cytotoxic T-cell activation (through evaluation of CD8+CD40+ and CD8+CD154+ cells), chemokine receptors (through evaluation of CD8+CD184+ and CD8+CD195+ cells), and adhesion molecules (through evaluation of CD8+CD152+ cells) which play a part in cell activation in blood and serum samples of patients with OLP and then to compare them with healthy controls. Methods: Thirty patients with OLP, and 30 matched healthy controls participated. The mean ages of OLP patients and controls were 51,10 +/- 12,25 and 48,09 +/- 11,92, respectively. Percentage of apoptotic cells, granzyme-B+, CD8+, CD8+CD40+, CD8+CD152+ (CTLA-4), CD8+CD154+(CD40L), CD8+CD184+(CXCR-4) and CD8+CD195+(CCR-5) were detected by immunophenotyping on flow cytometry. Apoptosis measurements were accomplished with Annexin V/Propidium Iodide kit. Results: A higher percentage of CD8+CD154+ and granzyme-B+ and a lower percentage of CD8+, CD8+CD184+ and apoptotic cells were found in OLP patients than in controls. No statistical differences were observed in the percentages of the other markers between groups. Conclusions: It is observed that because of increase in granzyme B+ and CD154 which is the activation marker, CD8+ cells present efforts to sustain their activity even though decrease in their cell number. Lower levels of CD8+CD184+ cells in OLP than control is evaluated as a factor that makes OLP to be localised in our study. In addition, our findings lead us to think that there may be some changes in apoptosis pathways of the cells. But this needs to be clarified by further studies exploring the mechanisms of the apoptosis in OLP patients.
Keywords: GRANZYME-B; PERIPHERAL-BLOOD; CTLA-4 RECEPTOR; SKIN DISEASES; IN-VIVO; APOPTOSIS; EXPRESSION; DEATH; KERATINOCYTES; CD40